Development of Interactive Teaching Materials Based on Articulate Storyline Software - Marwan Toni; Tobroni Tobroni; Faridi Faridi; Nurhakim Nurhakim (Al-Hayat: Journal of Islamic Education, 2024)
This development research aims to analyze learning media to create Islamic education teaching media with interactive media with the help of Articulate Storyline Software. Using research and development methods with qualitative and quantitative approaches, this research was conducted at SMAN 12 Berau as a subject and a test tool for the teaching media. The use of ADDIE as a procedure and guideline for developing teaching media. Data collection techniques by distributing surveys to test subjects and a series of formative assessments. The analysis technique uses qualitative and statistics. The results of the analysis of the development of these teaching materials are in the form of software products or Electronic Student Book (BSE) applications. The teaching material is suitable for use based on test results and analysis, which explains the survey results of design experts are 86%, media experts give a percentage of 87%, and materials experts consider 80%. Due to the development of teaching materials, Articulate Storyline Software can be easily used via a cellphone or laptop with an attractive appearance so that students will efficiently operate and learn by utilizing the application.